ضبط ومراقبة العملية الانتاجية باستخدام خرائط المراقبة الاحصائية للمتغيرات (حالة تطبيقية على معمل جود لتجميع الأدوات الكهربائية) - نتيفة هلا (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتناول هذا البحث بالدراسة والتحليل مسألة ضبط ومراقبة العملية الإنتاجية باستخدام خرائط مراقبة الجودة (لوحات السيطرة) للمتغيرات، بهدف قياس جودة المنتجات أثناء العملية الإنتاجية، وذلك عن طريق معرفة مقدار الانحرافات الحاصلة في العملية الإنتاجية وأسبابها وزمنها ومكانها واتخاذ الإجراءات التصحيحية المناسبة. ويعبِر عن خريطة مراقبة الجودة الإحصائية عرض بياني للقياسات عبر الزمن تُظهر الحدود الدنيا والعليا للعملية التي نريد مراقبتها وضبط جودتها وذلك للتمييز بين التغيرات الطبيعية التي تحدثها أسباب عامة كامنة في العملية وبين التغيرات التي تحدثها أسباب محددة. ويُركز البحث على أنواع خرائط مراقبة الجودة وتطبيقها على حالة عملية تم إجرائها على معمل جود لتجميع الأدوات الكهربائية، منها خرائط مراقبة المتغيرات (Control charts for Variables) والتي تضم خريطة الوسط الحسابي (X ̅-Chart), خريطة الانحراف المعياري (S-Chart), خريطة المدى (R-Chart), خريطة الوحدات (X-Chart) وغيرها، حيث تم حساب قيم خطوط الضبط للخرائط المدروسة ورسم الخرائط بالاستعانة ببرنامج (SPSS) الإحصائي. ويخلص البحث الى نتائج واقعية تؤكد افتقار شركة جود لتطبيق التقنيات الإحصائية في ضبط الجودة ومنها خرائط المراقبة الإحصائية كما لا توجد طريقة علمية واضحة مبنية على أسس رياضية متبعة في ضبط سير العملية الإنتاجية، وباعتبار أن شركة جود حاصلة على شهادات مقاييس الجودة السورية والأوروبية، كان لا بد من وضع مجموعة من التوصيات للشركة تتعلق باستخدام خرائط المراقبة الإحصائية في جميع المراحل الإنتاجية، ووضع برامج دورية تدريبية تطويرية متخصصة في مجال الجودة مع ضرورة ضم كادر إحصائي إلى الكوادر العاملة في الشركة وأهمية قياس مقدرة العمليات الإنتاجية لمعرفة قابليتها على تحقيق خاصية الجودة ضمن المواصفات المحددة واستخدام حدود ضبط باعتماد ستة انحرافات معيارية عن متوسط العملية. This research deals with study and analysis the issue of adjust and control the production process by using the Quality Control Charts (Control Panels) for variables , in order to measure products quality during production process , by knowing deviations amount occurring in production process , causes, time and place deviation then take appropriate corrective actions. the quality control charts show graphic measurements over time and show the lower, central, and upper limits of the process that we want to control and quality control in order to distinguish between natural changes that caused by general reasons inherent in the process and the changes that caused by specific reasons. The research focuses on kinds of Quality Control Charts, the case have been applied on Jood Factory for assembly electrical tools, such as Control Charts for variables which includes Average chart ( X ̅- chart ) , standard deviation chart (s ̅ – chart), range chart (R – chart), and units chart (X– chart), the control lines were drawn by using SPSS program. The research concludes realistic results confirm that the company doesn’t have an application of statistical techniques in quality control such as Quality Control Charts and there isn’t clear scientific method according to athletic basis followed in process control. Jood company has certificates of Syrian and European standards of quality control so it had to be a recommendation for the company related to use statistical control charts in all production stages , and put periodic developmental specialist training programs in quality control field with the need to include a statistical cadre to staff working in the company, and the importance of measuring process capability to make sure of its abilityto achieve quality within the specified standards, and use control limits of six standard deviation about process average.